Apoptotic Cells for Therapeutic Use in Cytokine Storm Associated With Sepsis– A Phase Ib Clinical Trial - van Heerden, Peter Vernon; Abutbul, Avraham; Sviri, Sigal; Zlotnick, Eitan; Nama, Ahmad; Zimro, Sebastian; el-Amore, Raja; Shabat, Yehudit; Reicher, Barak; Falah, Batla; Mevorach, Dror (Frontiers in Immunology, 2021)
Background. Sepsis has no proven specific pharmacologic treatment and reported mortality ranges from 30%–45%. The primary aim of this phase IB study was to determine the safety profile of Allocetra™-OTS (early apoptotic cell) infusion in subjects presenting to the emergency room with sepsis. The secondary aims were to measure organ dysfunction, intensive care unit (ICU) and hospital stays, and mortality. Exploratory endpoints included measuring immune modulator agents to elucidate the mechanism of action. Methods. Ten patients presenting to the emergency room at the Hadassah Medical Center with sepsis were enrolled to this phase Ib clinical study. Enrolled patients were males and females aged 51–83 years, who had a Sequential Organ Failure Assessment (SOFA) score >2 above baseline and had sepsis from a presumed infection. Allocetra™-OTS was administered as a single dose (day +1) or in two doses of 140×106 cells/kg on (day +1 and +3), following initiation of standard-of-care (SOC) treatment for septic patients. Safety was evaluated by serious adverse events (SAEs) and adverse events (AEs). Organ dysfunction, ICU and hospital stays, and mortality, were compared to historical controls. Immune modulator agents were measured using Luminex® multiplex analysis. Results. All 10 patients had mild-to-moderate sepsis with SOFA scores ranging from 2–6 upon entering the study. No SAEs and no related AEs were reported. All 10 study subjects survived while matched historical controls had a mortality rate of 27%. The study subjects exhibited rapid resolution of organ dysfunction and had significantly shorter ICU stays compared to matched historical controls (p<0.0001). All patients had both elevated pro-and anti-inflammatory cytokines, chemokines, and additional immune modulators that gradually decreased following treatment. Conclusion. Administration of apoptotic cells to patients with mild-to-moderate sepsis was safe and had a significant immuno-modulating effect, leading to early resolution of the cytokine storm. Trial registration. ClinicalTrials.gov Identifier: NCT03925857. https://clinicaltrials.gov/ct2/show/study/NCT03925857.